Ibuprofen use during extreme exercise: Effects on oxidative stress and PGE2 - McAnulty, S. R.; Owens, J. T.; McAnulty L. S.; Niemann, D. S.; Morrow, J. D.; Dumke, C. L.; Milne, G. L. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Oxidative stress was examined with use (N = 29) or nonuse (N = 25) of ibuprofen in ultramarathoners after the Western States Endurance Run.